The distribution of neuromuscular junctions depends on muscle pennation, when botulinum neurotoxin receptors and SNAREs expression are uniform in the rat. (June 2022) - Carré, Denis; Martin, Vincent; Kouidri, Yousra; Morin, Renaud; Norlund, Marine; Gomes, Aurélie; Lagarde, Jean-Michel; Lezmi, Stephane
Abstract : Background: Botulinum neurotoxins (BoNTs) are used to treat spastic disorders. Depending on muscle size, one or multiple injections are recommended according to labels to target neuromuscular junctions (NMJ). However, information about NMJ distribution and number in muscles, as well as expression of receptors and molecular targets of toxins is scarce in human and animal models. Methods: Seven muscles from adult rats were used to identify expression of BoNT receptors and SNAREs using immunohistochemistry (IHC), and fluorescent α-Bungarotoxin combined to light-sheet microscopy used to determine their distribution. Results: The location, number, and density of NMJ were muscle specific and mostly dependent on the type of pennation (myofiber orientation). In the Flexor Digitorum Brevis (a very small muscle) NMJ were as numerous as in the Gastrocnemius lateralis . A strong expression of SV2C, Synaptotagmin 2, SNAP25 and VAMP1 were observed in all muscles, and SV2A, Synaptotagmin 1 and VAMP2 were never detected. Conclusion: This work highlights the specific distribution of NMJ in muscles which seems to depend on the type of pennation. Detailed observation of myofibers organization might help clinicians to better evaluate the location of NMJ in humans; the molecular phenotyping of NMJ will contribute to better integrate the rat model into research of BoNT therapeutics. Graphical abstract: Image 1 Highlights: The location, number, and density of NMJ mostly dependent on the muscle pennation. NMJ are strongly positive for SV2C, Synaptotagmin 2, SNAP25 and VAMP1. NMJ are moderately positive for SV2B. NMJ are negative for SV2A, Synaptotagmin 1 and VAMP2. All muscles analyzed present with the same receptors and SNAREs distribution.